2014
DOI: 10.3390/nu6104073
|View full text |Cite
|
Sign up to set email alerts
|

Micronutrient Intakes among Children and Adults in Greece: The Role of Age, Sex and Socio-Economic Status

Abstract: The aim of the present study was to report the usual nutrient intakes of sixteen micronutrients by schoolchildren, adults and the elderly in Greece and to further explore the role of age, sex and socio-economic status (SES) on meeting the recommended nutrient intakes. Dietary intake, demographic and SES data from three existing studies conducted in Greece (in 9–13-year-old children; 40–60-year-old adults; and 50–75-year-old women) were collected. The prevalence of study participants with inadequate micronutrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
26
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 36 publications
8
26
0
5
Order By: Relevance
“…One of the main findings was that the consumption of the examined core food groups was below recommendations for the vast majority of children and adults. That could be one of the main reasons explaining the relatively high percentages of inadequate micronutrient intakes observed in the present study and discussed in detail elsewhere [ 25 ]. Regarding micronutrient intakes, the findings of the current study showed some clear sex- and age-specific differences, with intakes for the majority of the examined micronutrients being higher in females compared to males and in postmenopausal women compared to younger age groups.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…One of the main findings was that the consumption of the examined core food groups was below recommendations for the vast majority of children and adults. That could be one of the main reasons explaining the relatively high percentages of inadequate micronutrient intakes observed in the present study and discussed in detail elsewhere [ 25 ]. Regarding micronutrient intakes, the findings of the current study showed some clear sex- and age-specific differences, with intakes for the majority of the examined micronutrients being higher in females compared to males and in postmenopausal women compared to younger age groups.…”
Section: Discussionmentioning
confidence: 65%
“…As far as gender differences were concerned, the average intake for the majority of nutrients was found to be almost consistently higher for males compared to females, while the relevant percentages with inadequate dietary intakes were found to be higher for females compared to males. More detailed information on the age- and sex-specific differences observed in the present study have been described elsewhere [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…More information on the procedures followed to record and assess dietary intake is provided elsewhere [2,17]. Information on supplement usage was also collected as part of the 24 h recall interviews.…”
Section: Methodsmentioning
confidence: 99%
“…Deficiencies of micronutrients are prevalent among children in developing and some of the developed countries [1][2][3][4]. Low micronutrient intakes may link to long-term health risks [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Low micronutrient intakes may link to long-term health risks [5][6][7]. Recent European studies suggested that substantial numbers of European children might be at risk due to inadequate intake of micronutrients [4,8]. China's dietary changes are enormous [9,10] and the shifts in foods consumed and eating behaviors will continue to accelerate [11].…”
Section: Introductionmentioning
confidence: 99%